Managing the organisation 2.0: entrepreneurial spirit and general management competences as early indicators for cluster success and sustainable regional development: findings from the German Entrepreneurial Regions Programme - Gebhardt, Christiane; Pohlmann, Markus (The journal of high technology management research, 2013)
During the last twenty years the German programme family Entrepreneurial Regions has formed a landscape of strategy driven clusters, characterized by networking relationships along the value chain between SME, university and research laboratories. Initiated by the Federal Government the Entrepreneurial Regions Programme (ERP) was directed at rebooting East Germany's innovative strength and reviving the declined industrial basis as well as integrating the small technology oriented firms, remnants from GDR research labs into the global economy. The study carried out in 2010 and 2011 was based on a multi-method approach and went beyond traditional quantitative indicators such as turnover, job growth and number of patents, by focusing on interrelated qualitative and early indicators in a systemic approach. Apart from the continuity of Financial Investments, General Management Competences, Networking competences as well as Entrepreneurial Thinking and Acting were identified to be relevant key drivers for many other interconnected indicators of cluster development. We discuss the integration of Management Science into the context of regional innovation, organizational studies and industrial strategy and will shed light on the policy implications for the assessment and monitoring of clusters as well as on the management requirements of clusters. An outcome of our study is an indicator system that enriches the conventional indicator set for the evaluation of robustness and viability of politically initiated clusters.